PARAMETER CALIBRATION AND EXPERIMENT OF DISCRETE ELEMENT SIMULATION OF SPHERICAL-LIKE SOYBEAN BASED ON DEM - CHEN, Guangwei; LI, Fuxing; QU, FaYi; ZHANG, Chong Jian (INMATEH - Agricultural Engineering, 2024)
This paper focuses on the lack of spherical-like soybean simulation parameters when guiding the optimization and design of agricultural machinery and equipment through discrete element simulation. The spheroidal soybean variety SN29 was used as a study subject; the intrinsic properties and physico-mechanical properties of the spherical soybean were determined through actual measurements and the simulation of spherical-like soybean particles with Hertz-Mindlin (no-slip) as the contact model was established. The collision recovery, static, and rolling friction coefficients of the spherical-like soybean and acrylic sheet material were measured by the natural drop and inclined plane methods, combined with discrete element simulation and bench experiments. They were 0.474, 0.496, and 0.0361, respectively. The relative errors between the measured stacking angles and the simulated stacking angles were used as indicators, and the contact parameters between the particles were used as variables for the design of the steepest climb experiment. The collision recovery coefficient, static friction coefficient, and rolling friction coefficient between spherical-like soybean particles were determined to be 0.35, 0.30, and 0.074, respectively, by orthogonal rotational combination experiment and multi-objective optimization. The relative error between the simulated and measured stacking angles was only 1.09%, as verified by the experiment. This proves that the discrete element simulation parameters of the studied spherical-like soybean can reflect its real characteristics and be used as the parameter basis for discrete element simulation.